Microarray analysis of virulence gene profiles in Salmonella serovars from food/food animal environment - Wen Zou; Sufian F Al-Khaldi; William S Branham; Tao Han; James C Fuscoe; Jing Han; Steven L Foley; Joshua Xu; Hong Fang; Carl E Cerniglia; Rajesh Nayak (Journal of Infection in Developing Countries)
Introduction: Rapid, accurate and inexpensive analysis of the disease-causing potential of foodborne pathogens is an important consideration in food safety and biodefense, particularly in developing countries.  The objective of this study is to demonstrate the use of a robust and inexpensive microarray platform to assay the virulence gene profiles in Salmonella from food and/or the food animal environment, and then use ArrayTrackTM for data analysis.